Pedagogy, Positionality and Adult Education: Missing Links? - Miriam Zukas; Janice Malcolm (Adult Education Research Conference, 2001)
Adult educators in the UK are now covered by one of two sets of professional standards. Using our previously developed framework for evaluating pedagogic models, we examine the extent to which perspectives on, and assumptions about positionality are evident and the ways in which diversity is recognised by those standards.